Optimum density determination for bouguer correction using statistical methods: a case study from north of Iran - Eshaghzadeh, Ata; Kalantari, Roghayeh sadat; Moeini Hekmat, Zohreh (International Journal of Advanced Geosciences, 2015)
The main aim of initial gravity data processing is to determine the density of under-research geological structures and stratification mat rials in this case. The density is important for the calculation of the Bouguer plate and terrain corrections. To achieve the corrected gravity data with high quality and accuracy, exact estimation of the density is very significant, but representative optimum density value for an area of interest is notoriously difficult to obtain. In this paper, several statistical methods based on the correlation are proposed, such as variation and fractal for surface optimum density determination. The efficiency of the methods has been employed for a case study in north of Iran.